ANALYZING FACTORS THAT DRIVE CONSUMER PURCHASE INTENTION OF NYX SOFT MATTE LIP CREAM IN MANADO - Ulag, Pricilia Andreina; Tumbuan, Willem J.F.A; Rumokoy, Farlane S (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: NYX Professional Makeup Soft Matte Lip Cream offers a lightweight creamy lip color with fantastic durability power. It goes on smoothly and dries matte, locking in moisture. Consumer purchase intention is a willingness of a customer to purchase a certain products and also a kind of decision making to purchase a particular brand by customer. It is important to know the factors that drive consumer purchase intention in business, in order to guarantee business continuity and to survive from the competitors. The objective of this research is to define the factors that drive consumer purchase intention of NYX Soft Matte Lip Cream in Manado. Quantitative research seeks to quantify the data. Data was collected using questionnaire that distributed to 100 respondents. Analysis method is used in this research. The result from this research is there are 17 variables that correlated with the factor that already conducted. The results from the factoring process are 2 factors that drive consumer purchase intention. The first factors Product Knowledge with 12 independents variables and the second factor is Customer Experience with 5 independent variables.Â Â Keywords: consumer purchase intention, product knowledge, customer experience